Empowering the Cadre of Pregnant Women Control Program to Prevent Anemia - Sari, Levi Tina; Renityas, Nevy Norma; Noviasari, Ita (Journal of Community Service for Health, 2021)
Anemia in pregnant women was one of the national health problems and has the potential to be dangerous for the fetus and pregnant women. So, the role of cadres was needed as the front line for early detection or screening in the community. The method used the provision of material with lectures and discussions, the gathered of cadres used a health protocol, where the provision of material lasts for 2 hours. As a result, it was known that there had been a change in knowledged and attituded of caregivers in the prevention and management of pregnant women related to anemia, and it was known that cadres who did not work would play an active roled in posyandu activities. Therefore, it was expected that Posyandu cadres will received seminars or trained in accordance with their respective fields. So that the implementation of health serviced in the community could be optimal